Анализ полиморфных вариантов С677Т и А1298С гена MTHFR у больных псориазом - Федота, А.М.; Рощенюк, Л.В.; Адмакина, А.В.; Солодянкин, А.С. (Фактори експериментальної еволюції організмів, 2015)
Aim. Analysis of DNA samples for the study of psoriasis patients SNP C677T and A1298C gene methylenetetrahydrofolate reductase (MTHFR). Methods. Genealogical analysis of 201 probands and relatives was carried out. Genomic DNA of 201 patients was analyzed by polymerase chain reaction. Testing statistical hypotheses about the association studied genotypes with disease and evaluation of equality of distribution series conducted using χ2 test at a signifi cance level of 0.05, 0.01 and 0.001. Results. Population structure corresponds to the correlation of the Hardy-Weinberg balance, the actual distribution of genotypes was not signifi cantly different from the theoretically expected at balance C677T polymorphisms (df = 2, st = 5.99, f = 3.04, p > 0,05) and A1298C (df = 2, st = 5.99, f = 3.54, p > 0.05). Analysis of the distribution series genotype frequencies for polymorphisms C677T and A1298C MTHFR gene in patients showed a statistically significant difference between the theoretically expected and actual frequencies (F = 44.0, p < 0.001). Conclusion. The sample of patients with psoriasis shows deviations from balance by combinations of genotypes that are analyzed in the positions of the C677T and A1298 gene MTHFR. Such deviation from balance may mean that some genotypes carriers probably have a selective advantage, others — low adaptability.